Rope skipping or badminton? exercise reduced sleep onset latency in university students - Ye, Zixin; Tan, Shuyue; Zhu, Yingyuan; Fan, Jialin (Frontiers in Sports and Active Living, 2025)
IntroductionPoor sleep quality is common among university students and can negatively affect their physical and mental health. Aerobic exercise has shown promise in mitigating these issues. Exercise interventions involved in previous studies were often time-consuming. To identify a more efficient approach, we evaluated the effects of 13-day rope skipping and badminton interventions on sleep issues. We hypothesized that both badminton and rope skipping could effectivly improve sleep problems and that the effect of rope skipping would be greater than that of badminton.MethodsFifty-five participants’ levels of sleep were assessed via nine variables, using the Consensus Sleep Diary and the Pittsburg Sleep Quality Index.ResultsBoth exercises were effective in improving sleep onset latency. Badminton has a greater effect on improving daytime dysfunction than rope skipping. No additional significant results were found on the other components of sleep. One of the reasons for the nonsignificant results could be that some participants’ sleep was disturbed by their roommates sharing the same bedroom.DiscussionShort-term rope skipping and badminton are competitive interventions in improving sleep quality for university students. Some participants reported being more interested in exercise after the intervention, suggesting that exercise interventions could be used to foster exercise habits.